1967
DOI: 10.3181/00379727-124-31989
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Biliary Metabolites of Orally Administered Ethynylestradiol (EE) and its 3-Cyclopentyl Ether (EECPE-Quinestrol)

Abstract: Preliminary experiments showed that measurable amounts of radioactivity appear in the bile of the rat shortly after oral administration of aqueous suspensions of isotopically labeled EE or EECPE. The observation that as much as 45% of the administered dose of EE and 27% of that of EECPE could be recovered from the 2s-hour bile samples indicated that the 2 compounds or their metabolites undergo an active enterohepatic circulation. It seemed, therefore, worthwhile to investigate the nature, distribution and biol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

1968
1968
2010
2010

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 2 publications
1
7
0
Order By: Relevance
“…At 24 h the results with the larger dose were variable (one out of two animals) and 5 mg/kg was without effect in this time. Although this may be partly due to dose dependence it seems unlikely that the steroid does not reach the liver during this time as Steinetz, Meli, Giannina & Beach (1967b) showed that 58% of a tracer dose of labelled ethinyloestradiol, given orally to rats, was secreted into the bile in 5 h, 45% being accounted for in the first 2-5 h. Moreover, when ethinyloestradiol and lynoestrenol were given intravenously to assure absorption. bile secretion was also unimpaired.…”
Section: Discussionmentioning
confidence: 99%
“…At 24 h the results with the larger dose were variable (one out of two animals) and 5 mg/kg was without effect in this time. Although this may be partly due to dose dependence it seems unlikely that the steroid does not reach the liver during this time as Steinetz, Meli, Giannina & Beach (1967b) showed that 58% of a tracer dose of labelled ethinyloestradiol, given orally to rats, was secreted into the bile in 5 h, 45% being accounted for in the first 2-5 h. Moreover, when ethinyloestradiol and lynoestrenol were given intravenously to assure absorption. bile secretion was also unimpaired.…”
Section: Discussionmentioning
confidence: 99%
“…However, the origin of the cecal 6-bromo-2-naphthyl-j3-glucosidase and -P-galactosidase activities was not determined. small extent following their infusion into the small intestine (50). Extensive enterohepatic circulation of diethylstilbestrol has been shown to take place in the rat (51).…”
Section: Reactionsmentioning
confidence: 99%
“…The metabolism of ethynyloestradiol in rats has been extensively studied (5). Most of the radioactivity in plasma was present as a sulphate in that radioactivity could only be extracted after solvolysis.…”
Section: Discussionmentioning
confidence: 99%